Desain Sistem Kontrol Container Station Menggunakan Metode Waterfall Berbasis Internet of Things (IoT) - Yuliadi Erdani; Rizqi Aji Pratama; Ginna Intan Fadila; Bahdin Ahad Badia (Universitas Islam Raden Rahmat, Malang, 2024)
The development of Internet of Things (IoT) technology has created new opportunities for optimizing container logistics systems. IoT enables physical devices to connect to the internet, facilitating real-time data exchange and remote control. This research aims to design a control and monitoring system for container stations based on IoT using NodeMCU as an intermediary to integrate PLC devices with the IoT network. The waterfall method ensures systematic system development from requirements analysis, system design, implementation, testing, to maintenance. Data transmission utilizes the MQTT protocol. Test results demonstrate successful integration between PLC devices and the IoT network via NodeMCU. The Blynk application facilitates control and monitoring of container stations, allowing users to easily interact via push buttons and LEDs.